THE WATER SECTOR'S EVOLUTION: KEY CHALLENGES AND FUTURE PROSPECTS - García, María Elena Fernández (Economics and Statistics Research Journal (ESRJ), 2024)
Water supply utilities, once operating under the radar, are now facing increased scrutiny due to rising standards for drinking water and environmental protection, alongside heightened public awareness and financial challenges. This scrutiny has led to a diminishing confidence in the competence and sustainability of these utilities. Despite these challenges, the water industry remains a significant and expanding sector whose economic impact is becoming more apparent. The industry, characterized by diverse growth rates across its various segments, is increasingly consolidating and evolving into a more cohesive and unified field. This study examines the current state of the water supply utilities sector, highlighting the pressures driving changes and the implications for its future development. By analyzing the trends and transformations within the industry, the research aims to provide a comprehensive understanding of its economic significance and the ongoing shifts towards a more integrated approach